1983
DOI: 10.1111/j.1365-2125.1983.tb02090.x
|View full text |Cite
|
Sign up to set email alerts
|

Dystonic reactions and the pharmacokinetics of metoclopramide in children.

Abstract: Newcastle upon Tyne, NE1 7RUThe pharmacokinetics of metoclopramide have been studied in nine children receiving the drug as prophylaxis for cytotoxic induced vomiting. Plasma concentrations of metoclopramide have also been studied in three children with dystonic reactions to the drug. The pharmacokinetics in children were similar to those reported in healthy adults. There was no difference in the plasma concentration of metoclopramide of children with dystonia when compared to those without this adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 9 publications
1
31
1
1
Order By: Relevance
“…) Pharmacokinetic considerations may contribute to preo disposing factors in individuals susceptible to neurolepticinduced dystonia. Plasma drug levels do not differentiate between dystonic and non-dystonic patients (Garver et al 1976;Tune and Coyle 1981;Bateman et al 1983). However, measurement of membrane-bound neuroleptic drug concentration in red blood cells in one study of butaperazine revealed increased erythrocytic drug levels in dystonic patients as compared to those in neuroleptic-treated patients not developing dystonic reactions (Garver et al 1976).…”
Section: Incidencementioning
confidence: 99%
“…) Pharmacokinetic considerations may contribute to preo disposing factors in individuals susceptible to neurolepticinduced dystonia. Plasma drug levels do not differentiate between dystonic and non-dystonic patients (Garver et al 1976;Tune and Coyle 1981;Bateman et al 1983). However, measurement of membrane-bound neuroleptic drug concentration in red blood cells in one study of butaperazine revealed increased erythrocytic drug levels in dystonic patients as compared to those in neuroleptic-treated patients not developing dystonic reactions (Garver et al 1976).…”
Section: Incidencementioning
confidence: 99%
“…Acute dystonia usually occurs three to five days after antipsychotic therapy begins or the dosage is increased [10]. Although there was a history of metoclopramide overdose in our patient, it is reported that there was no difference in plasma concentration of metoclopramide of children with dystonia when compared to those without this side effects [7]. Our patient did not receive any other drug other than metoclopramide.…”
Section: Discussionmentioning
confidence: 70%
“…Cezard et al reported that there is no dose-effect correlation and sex has no influence on the occurrence of neurological symptoms [6]. Bateman et al reported that there was no difference in plasma concentration of metoclopramide of children with dystonia when compared to those without these side effects [7]. Hyser et al reported that metoclopramide clearance is reduced in renal failure, and myoclonus or other neurologic complications may be precipitated in such patients by usual doses of this drug [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be noted that the removal of cisapride from the therapeutic choices would leave metoclopramide, erythromycin, and domperidone as primary treatment options. These alternate drugs are also not without potentially severe side effects, also including prolongation of the QT interval [26,27,28,29]. Recently, the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition reconfirmed that "cisapride has a place in pediatric therapeutics when used in conditions in which a prokinetic drug is indicated" [30].…”
Section: Discussionmentioning
confidence: 98%